Evaluación del clima laboral en áreas administrativas del Hospital General San Vicente de Paúl - Benavides Rosero, Amparo Del Rocío (2025)
he work environment is a relevant component in public and private organizations, which requires permanent evaluation that allows to value in direct and subjective way, the perception that human talent has regarding the components: leadership, commitment and work environment. The general objective of this research was to evaluate the work environment in the administrative areas of the San Vicente de Paúl General Hospital, observing and applying the methodology proposed by the Ministry of Labor. The methodological design that was applied according to the modality was mixed: qualitative – quantitative that allowed the analysis of data from the application of the work environment evaluation questionnaire; according to the scope, descriptive-analytical research was applied to establish the interpretation of the fundamental characteristics of the work environment components using statistical graphs and tables; from the design point of view it was non-experimental, transversal considering that the evaluation was done in the operational period 2024. The population subject to study were the 69 career public workers and contracted personnel from the administrative areas of this institution. The research technique was the survey for the evaluation of the work environment, using a questionnaire in accordance to the Regulations of the Ministry of Labor. The results obtained from the work environment assessment determine that the components: leadership, commitment and work environment have a very good rating, so that, it is necessary to establish policies and actions for continuous improvement and achieve productivity levels.